Use of spectral reflectance to discriminate between potassium deficiency and orange spotting symptoms in oil palm (Elaeis guineensis) - Selvaraja, S.; Balasundram, Siva Kumar; Vadamalai, G.; Mohd Hanif, Ahmad Husni (Marsland Press, 2013)
Potassium (K) deficiency and Orange Spotting (OS) disease exhibit similar symptom via visual assessment. This work investigates the separability of K deficiency and OS disease symptoms using spectral reflectance. This assessment was conducted at a commercial oil palm plantation located in Sungai Buloh, Selangor. Leaves from K-deficient trees, OS-infected trees and nonsymptomatic trees (control) were sampled for spectral reflectance acquisition. Leaf spectral reflectance was acquired under constant halogen lighting. All leaf samples exhibited a green peak at 555 nm wavelength, with an average reflectance value of 0.15. Reflectance between OSinfected and K-deficient leaves showed significant separability at the 400-538 nm and 667-688 nm wavelength regions. Reflectance of K-deficient leaves was significantly different than that of OS-infected leaves across all severity classes.